CHOICE OF THE METHOD OF RECOVERY OPERATION IN SHORT RIGHT PARTS OF THE COLON - V. I. Pomazkin; G. A. Zobnina (Вестник хирургии имени И.И. Грекова, 2016)
The results of treatment were analyzed in 41 patients (the mean age 62,1 years old). Overall postoperative lethality consisted of 2,4%. The best functional results were reached in transmesenteric bringing down of the right parts of colon to small pelvis with isoperistaltic colorectal anastomosis. However, an application of this operation demands the presence of certain anatomic conditions. Limited mobilization of the right colon with antiperistaltic cecorectal anastomosis is feasible under any conditions.